Fabrication of a high performance memristor device by metallization of Ag+ inside a solution processed Li5AlO4 thin film - Pramanik S.; Chakraborty R.; Hazra S.; Pandey U.; Pal B.N. (My University, 2025)
A solution processed Ag-ion-exchanged Li5AlO4 thin film has been used to fabricate a high performance oxide memristor device with enhanced bistable switching and memory retention. For this device fabrication, an Li5AlO4 thin film has been deposited on a highly p-doped silicon (p+-Si) substrate followed by an ion exchange and reduction process that allows the conversion of the Li5AlO4 thin film to an Ag(Ag+)-Al2O3 film. The Ag(Ag+)-Al2O3 film is a mixed phase consisting of an Ag nanoparticle embedded Al2O3 film and silver ions and is responsible for resistive switching whereas the p+-Si substrate works as the bottom electrode. A silver electrode has been used on top of Ag(Ag+)-Al2O3/p+-Si that works as the top electrode of this memristor device. The I-V characteristics of the device demonstrate a reversible switching behaviour that remains stable even after 200 consecutive operation cycles. Furthermore, the ratio between the forward and reverse sweeps of the device exceeds 103 orders of magnitude and the device has a stable data retention capability of ∼4 × 104 seconds (∼12 hours) maintaining its on/off ratio of ∼104. Also, this device effectively emulates the properties of ReRAM up to 200 iterations. © 2024 The Royal Society of Chemistry.